Postoperative Complications of Free Flap Reconstruction in Moderate-Advanced Head and Neck Squamous Cell Carcinoma: A Prospective Cohort Study Based on Real-World Data - Li, Delong; Wang, Chong; Wei, Wei; Li, Bo; Liu, Huan; Cheng, Aoming; Niu, Qifang; Han, Zhengxue; Feng, Zhien (Frontiers in Oncology, 2022)
Background: Postoperative complications (POCs) of moderate-advanced head and neck squamous cell carcinoma (HNSCC) after free flap reconstruction have received little attention. We investigated the risk factors that lead to POCs and their impact on management and prognosis. Patients and Methods: A single-center, prospective cohort study was conducted at Beijing Stomatological Hospital on primary HNSCC patients treated between 2015 and 2020. Results: In total, 399 consecutive HNSCC patients who underwent radical resection of the primary tumor and free flap reconstruction were enrolled in this study, 155(38.8%) experienced POCs. The occurrence of POCs directly led to worse short-term outcomes and poorer long-term overall survival (P=0.0056). Weight loss before the operation (P=0.097), Tumor site (P=0.002), stage T4b (P=0.016), an ACE-27 index of 2-3 (P=0.040), operation time≥8h (P=0.001) and Clindamycin as antibiotic prophylaxis (P=0.001) were significantly associated with POCs. Conclusions: The occurrence of POCs significantly leads to worse short-term outcomes and increases the patients’ burden.